Liver involvement in NGLY1 congenital disorder of deglycosylation - Lipiński, Patryk; Cielecka-Kuszyk, Joanna; Socha, Piotr; Tylki-Szymańska, Anna (Polish Journal of Pathology, 2020)
N-glycanase 1 deficiency is a congenital disorder of deglycosylation, which has been diagnosed in 27 patients, including 2 of them from Poland. The most characteristic symptoms include global developmental disability, hyperkinetic movement disorder, hypo-/alacrimia, and elevated serum transaminases. We reported on a patient in whom the liver biopsy done at the age of 3 years revealed the presence of steatosis, fibrosis, and an amorphous periodic acid-Schiff staining positive diastases-digested material in the cytoplasm.